2009
DOI: 10.1007/s10880-009-9162-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cognitive and Behavioural Treatment of Chronic Pain in the Elderly: A Quantitative Review

Abstract: This study provides a meta-analytic review of cognitive and behavioural interventions for chronic pain in the elderly, focusing on treatment effectiveness. Included in the analysis are studies in which a comparison was made either to a control condition or to pre-treatment. A total of 12 outcome studies published or reported between January 1975 and March 2008, were identified involving participants 60 years and above and providing 16 separate treatment interventions. The analysis indicated that cognitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 41 publications
0
35
0
3
Order By: Relevance
“…A review of the effectiveness of cognitive and behavioral treatment for chronic pain in older people concluded that, based on 16 separate treatment comparisons, these treatments produce a small or near medium sized effect on reported pain but no effect on depression, physical functioning, or medication use (14). More encouraging results were achieved in a more recent study by Nicholas and colleagues (6).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the effectiveness of cognitive and behavioral treatment for chronic pain in older people concluded that, based on 16 separate treatment comparisons, these treatments produce a small or near medium sized effect on reported pain but no effect on depression, physical functioning, or medication use (14). More encouraging results were achieved in a more recent study by Nicholas and colleagues (6).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a review of the literature, McIntosh et al documented good agreement between a functional assessment interview and experimental methods. Rather than discounting closed-ended interviews and rating scales completely, practitioners should be aware that the reliability and validity of the assessment depends in large part on the skill of the assessor and on the knowledge and goals of the individual completing the rating scale or being interviewed (Haynes, Kaholokula, & Yoshioka, 2008;Lydon, Healy, O'Reilly, & Lang, 2012;Suen & Rzasa, 2004). Further, instruments should be used for the population for which they were intended.…”
Section: A Hierarchical Approach To Functional Assessmentmentioning
confidence: 99%
“…This issue has been examined in the context of functional analysis in a handful of studies, almost exclusively with individuals with disabilities. Several studies have demonstrated differential outcomes across settings or therapists (Anderson & Long, 2002;English & Anderson, 2004;Gardner, Spencer, Boelter, Dubard, & Jennett, 2012 [working with typically developing individuals]; Lang et al, , 2009. Thomason-Sassi, Iwata, and Fritz (2011) attempted to clarify this issue with 6 individuals with developmental delay.…”
Section: Questions Surrounding the Implementation Of Functional Analymentioning
confidence: 99%
See 2 more Smart Citations